Psychosocial occupational health an interdisciplinary textbook - Siegrist, Johannes 1943-; Li, Jian 1974- (Oxford University Press, 2024)
A comprehensive and interdisciplinary review of the challenges of modern work and its impact on health, bringing together evidence from the fields of occupational medicine, social and behavioural sciences, and biomedical research.
Keywords: Arbeitspsychologie; Arbeitsplatz; Psychosoziale Situation